1994
DOI: 10.1177/0044118x94025004004
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Probation Intervention on Juvenile Offenders' Self-Concepts, Loci of Control, and Perceptions of Juvenile Justice

Abstract: This article examines the impact of job preparation, short-term outdoor adventure, and family relationships programming on juvenile probationers' self-concepts, loci of control (internal versus external), and perceptions of juvenile justice. Traditional probation services constitute the standard for comparison. After establishing the rationale for selection of the three dependent variables and describing how the intervention addressed these variables, the authors present data derived from a two-factor experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
1
15
1
Order By: Relevance
“…Our search identified 15 studies that evaluated the effects of physical activity programmes on social and emotional well-being in at-risk children and adolescents (Table 1). Seven studies evaluated the effects of outdoor adventure programmes (Bloemhoff, 2006;Cross, 2002;Green, Kleiber, & Tarrant, 2000;Kaiser, Smith, Heleski, & Spence, 2006;Minor & Elrod, 1994;Pommier & Witt, 1995;Wu & Hsieh, 2006), seven studies evaluated the effects of sport and skill-based interventions (Basile, Motta, & Allison, 1995;Bonnette, McBride, & Tolson, 2001;Goodway & Rudisill, 1996;Maiano, Ninot, Morin, & Bilard, 2007;Palermo et al, 2006;Robinson et al, 2009;Tester, Watkins, & Rouse, 1999) and two studies reported the effects of physical fitness programmes (Basile et al, 1995;Collingwood, Sunderlin, & Kohl, 1994). The majority of studies evaluated the effects of programmes among older children and adolescents, however, two studies (Goodway & Rudisill, 1996;Robinson et al, 2009) reported the effects of motor skill interventions in at-risk preschool children.…”
Section: Overview Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Our search identified 15 studies that evaluated the effects of physical activity programmes on social and emotional well-being in at-risk children and adolescents (Table 1). Seven studies evaluated the effects of outdoor adventure programmes (Bloemhoff, 2006;Cross, 2002;Green, Kleiber, & Tarrant, 2000;Kaiser, Smith, Heleski, & Spence, 2006;Minor & Elrod, 1994;Pommier & Witt, 1995;Wu & Hsieh, 2006), seven studies evaluated the effects of sport and skill-based interventions (Basile, Motta, & Allison, 1995;Bonnette, McBride, & Tolson, 2001;Goodway & Rudisill, 1996;Maiano, Ninot, Morin, & Bilard, 2007;Palermo et al, 2006;Robinson et al, 2009;Tester, Watkins, & Rouse, 1999) and two studies reported the effects of physical fitness programmes (Basile et al, 1995;Collingwood, Sunderlin, & Kohl, 1994). The majority of studies evaluated the effects of programmes among older children and adolescents, however, two studies (Goodway & Rudisill, 1996;Robinson et al, 2009) reported the effects of motor skill interventions in at-risk preschool children.…”
Section: Overview Of Studiesmentioning
confidence: 99%
“…Few studies provided stratified baseline characteristics and four studies did not include a control group or comparison group (Collingwood et al, 1994;Kaiser et al, 2006;Tester et al, 1999;Wu & Hsieh, 2006). Although a number of studies were randomised controlled trials (Basile et al, 1995;Goodway & Rudisill, 1996;Minor & Elrod, 1994;Palermo et al, 2006), only one study described the process of randomisation (Basile et al, 1995). Six studies used quasi-experimental designs (Bloemhoff, 2006;Bonnette et al, 2001;Cross, 2002;Green et al, 2000;Maiano et al, 2007;Robinson et al, 2009).…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
See 3 more Smart Citations